Observation of compact ferrimagnetic skyrmions in DyCo3 film. Issue 35 (27th August 2020) - Chen, K.; Lott, D.; Philippi-Kobs, A.; Weigand, M.; Luo, C.; Radu, F.
Abstract : The ferrimagnetic skyrmions, which are formed in DyCo3 during the nucleation/annihilation of the magnetic labyrinth domains, exhibit a topological Hall effect contribution, antiparallel aligned Dy and Co magnetic moments, and a core radius of about 40 nm. Abstract : Owing to the experimental discovery of magnetic skyrmions stabilized by the Dzyaloshinskii–Moriya and/or dipolar interactions in thin films, there is a recent upsurge of interest in magnetic skyrmions with antiferromagnetic spins in order to overcome the fundamental limitations inherent with skyrmions in ferromagnetic materials. Here, we report on the observation of compact ferrimagnetic skyrmions for the class of amorphous alloys consisting of 4f rare-earth and 3d transition-metal elements with perpendicular magnetic anisotropy, using a DyCo3 film, that are identified by combining X-ray magnetic scattering, scanning transmission X-ray microscopy, and Hall transport technique. These skyrmions, with antiparallel aligned Dy and Co magnetic moments and a characteristic core radius of about 40 nm, are formed during the nucleation and annihilation of the magnetic maze-like domain pattern exhibiting a topological Hall effect contribution. Our findings provide a promising route for fundamental research in the field of ferrimagnetic/antiferromagnetic spintronics towards practical applications.